Icings and groundwater conditions in permafrost catchments of northwestern Canada - Hugo Crites (Nature Portfolio, 2020)
Abstract Icings are sheet-like masses of ice that form on the ground surface or in fluvial channels from groundwater seepage. Although the presence of icings in the landscape is known, few studies investigated their regional distribution and explored relations with terrain factors including permafrost and winter baseflow conditions. Here, we mapped the distribution of icings in a 618,430 km2 area of northwestern Canada from a stack of 573 Landsat imageries (1985–2017) and determined using hydrometric data the winter baseflow contribution to the total annual discharge of 17 rivers in the study area. The 1402 mapped icings occur preferentially at the foothills of heavily faulted karstic mountainous regions in the continuous permafrost. Winter baseflow and its contribution to annual discharge was lower in continuous permafrost catchments than in discontinuous permafrost but showed a general increase over the 1970–2016 period. As such, the distribution of icings appears to be sensitive to winter air temperatures and winter baseflow conditions and icings located at the southern boundary of continuous permafrost would be more sensitive to degrading permafrost and the predicted increase in winter baseflow.